The effect of centromere protein U silencing by lentiviral mediated RNA interference on the proliferation and apoptosis of breast cancer - Lin, Shuang-Yan (Oncol Lett, 2018)
Centromere protein U (CENPU) is a novel transcriptional repressor that is associated with different types of cancer. However, its function in breast cancer is poorly understood. In the present study, it was identified that CENPU was highly expressed in breast cancer tissues compared with expression in normal breast tissues (P=0.001). Furthermore, the CENPU mRNA level in tumors was often elevated, compared with the matched adjacent normal breast cancer tissue specimens in the dataset from The Cancer Genome Atlas database (n=106; P<0.001). To understand the function of CENPU in human breast carcinogenesis, its effects on the proliferation, apoptosis and cell cycle progression of MDA-MB-231 cells were examined using the lentiviral-mediated CENPU knockdown approach. The RNA and protein expression levels in the transfected cells were monitored using reverse transcription-quantitative polymerase chain reaction and western blotting, respectively. The mRNA and protein expression levels of the CENPU gene were significantly lower in the CENPU-shRNA transfected cells than in the control (P<0.01), indicating successful gene expression knockdown. Post-transfection, cell counting and MTT analysis revealed that the proliferation activity was significantly suppressed in CENPU knockdown cells relative to the control (P<0.01). Additionally, fluorescence activated cell sorting analysis revealed that the (G2+S) phase fraction was significantly declined in CENPU knockdown cells relative to the control; while the G1 phase fraction was significantly increased (P<0.01) and the percentage of the apoptotic cells was significantly increased (P<0.01). In conclusion, downregulation of CENPU gene expression may inhibit cell proliferation and cell cycle progression, and increase the apoptosis of the breast cancer cells. These results suggested a possible function of this protein in breast cancer pathogenesis and prognosis.